Zygomaticomaxillary suture maturation: A predictor of maxillary protraction? Part I ‐ A classification method. (May 2017) - Angelieri, F.; Franchi, L.; Cevidanes, L. H. S.; Hino, C. T.; Nguyen, T.; McNamara, J. A.
Structured Abstract: Objective: The aim of this study was to present a method of classifying the maturational level of the zygomaticomaxillary sutures (ZMSs). Methods: Cone‐beam CT (CBCT) images from 74 subjects (5.6‐58.4 years) were examined to define the radiographic stages of ZMS maturation. Five stages of maturation of the ZMS were identified and defined: Stage A—uniform high‐density sutural line, with no or little interdigitation; Stage B—scalloped appearance of the high‐density sutural line; Stage C—two parallel, scalloped, high‐density lines, separated in some areas by small low‐density spaces; Stage D—fusion in the inferior portion of the suture; and Stage E—complete fusion. Intra‐ and inter‐examiner agreements were evaluated by weighted kappa tests. Results: The intra‐ and inter‐examiners reproducibility values demonstrated substantial to almost perfect agreement. No fusion of ZMSs was observed in patients up to 10 years of age. From 10 to 15 years, all maturational stages were identified. After 15 years of age, the majority of patients showed fusion of ZMSs. Conclusions: The classification of ZMS maturation using CBCT is a reliable method that allows the assessment of the morphology of the ZMSs in the individual patient.